Alcohol septal ablation as a modern and alternative treatment in patients with obstructive hypertrophic cardiomyopathy - K. Rudenko; L. Nevmerzhytska; O. Trembovetska; S. Fanta; V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2016)
The results of 132 alcohol septal ablation procedures in patients with obstructive hypertrophic cardiomyopathy are presented. Short-term and long term results showed that the procedure of alcohol septal ablation could be an alternative treatment to surgery and dual chamber pacing if coronary anatomy is appropriate.